2022
DOI: 10.1097/inf.0000000000003458
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Disclosure, Adherence and Viral Suppression in Children and Adolescents Living With HIV in Ecuador

Abstract: Background: Studies on HIV disclosure and adherence among children performed in Latin America are anecdotal. We aimed to assess the factors associated with HIV disclosure, adherence and viral suppression among Ecuadorian children and compare the psychologic consequences and the impact on adherence and viral suppression of early against late disclosure age. Methods: Cross-sectional study using a questionnaire and collected data on medical records of HIV-infected children between 6 and 21 years of age in Ecuad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The inconclusive result on this association needs to be further assessed in large and diverse samples in future studies. Further, the association between nonadherence and virological failure has been well proven in previous studies [32,34,35].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The inconclusive result on this association needs to be further assessed in large and diverse samples in future studies. Further, the association between nonadherence and virological failure has been well proven in previous studies [32,34,35].…”
Section: Discussionmentioning
confidence: 60%
“…Some factors were found to be associated with virological failure, including age of 14-17, being female, and having missed doses in the past month. Some previous studies also found that older children had a higher risk of virological failure [32,33], which could be explained by the poorer adherence and higher likelihood of drug resistance in older children [34]. Future studies are still needed to further testify this association and verify the reasons between age and virological failure because other previous studies did not detect this association [35,36].…”
Section: Discussionmentioning
confidence: 98%
“…The inconclusive result on this association needs to be further assessed in large and diverse samples in future studies. Further, the association between nonadherence and virological failure has been well proven in previous studies [ 39 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 63%
“…Some factors were found to be associated with virological failure, including age of 14–17, being female, and having missed doses in the past month. Some previous studies also found that older children had a higher risk of virological failure [ 39 , 40 ], which could be explained by the poorer adherence and higher likelihood of drug resistance in older children [ 39 , 41 ]. Future studies are still needed to further testify this association and verify the reasons between age and virological failure because other previous studies did not detect this association [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the elements linked to better adherence is the disclosure of HIV status. However, the prevalence of disclosure in children and adolescents varies depending on the environment and the age of the patients, ranging from 13 to 60% in children between the ages of 5 and 17 from Asia or Southern-Eastern Africa [ 1 ].…”
Section: Introductionmentioning
confidence: 99%